LEXICAL COHESION ANALYSIS OF PRESIDENT PRABOWO SUBIANTO'S SPEECH AT AL-AZHAR UNIVERSITY CAIRO DECEMBER 2024 - Asegaf , Husein; Sholihah, Husniatin; Novi Andriyani, Bernadeta; Dewi Handayani, Waode; Utami, Sri (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This research analyzes lexical cohesion in Prabowo Subianto's presidential speech at Al-Azhar University Cairo in December 2024. By using descriptive qualitative method, this research aims to identify and analyze the types of lexical cohesion applied, including repetition, synonymy, antonymy, hyponymy, collocation, and equivalence. The data of this research comes from the transcription of speeches uploaded through the YouTube channel Kompas.com. The analysis shows that repetition is the most dominant type of lexical cohesion used. Out of 78 data, repetition is found as much as 50 data, synonymy 3 data, antonymy 3 data, hyponymy 1 data, collocation 13 data, and equivalence 8 data. The dominant use of repetition reflects President Prabowo's efforts to strengthen his message and ensure the listeners' deep understanding. The key points in the repetition reflect the fundamental principles and identity of the Indonesian nation in the context of international relations, including mutual respect, rejection of hostility, and the essence of inclusive cooperation regardless of differences in order to realize unity and prosperity. This study concludes that lexical cohesion plays a significant role in building discourse cohesion and clarifying meaning in President Prabowo's speech. The careful selection of words based on semantic relationships contributes to the effective delivery of the message and the meaning of the speech.